Carl Ritter von Ghega - 2018 surveyor of the year : Carl Ritter von Ghega - geodet godine 2018. - Paar, Rinaldo (Array, 2020)
Carl Ritter von Ghega was proclaimed 2018 Surveyor of the Year on 21 March 2018. In this paper, we explore how this Austrian of Albanian extraction, born in Venice, played an important role in geodesy and the surveying profession and the honours he got up to the present day. We investigate his background and details of his professional path, education and most important contributions in the areas of surveying and engineering at large. We describe his most significant achievement, that is, the Semmering Railway, which was dismissed at the time as impossible to achieve. In 1998, the Semmering Railway was inscribed in the UNESCO World Heritage List. Apart from this project, which left a great impression on the engineering profession, von Ghega also developed the Borovnica Viaduct built in the mid-19th century in Slovenia.